A novel approach for very early pregnancy diagnosis in swine by anti-early pregnancy factor (EPF) antiserum blocking enzyme-linked immunosorbent assay (ELISA) - Kai Quan; Xingxu Zhao; Changxing Zhang; Qiuliang Xu; Hongfang Wei; Junjie Hu; Yong Zhang (African Journal of Pig Farming, 2014)
Early pregnancy factor (EPF) is essential for the initiation and maintenance of pregnancy. Early pregnancy factor activity monitoring has been reported to be the effective method for very early pregnancy diagnosis. In this study, three BALB/c mice were immunized with the synthetic peptide segment corresponding to the amino acid sequence 36 to 55 of EPF (IG20) for anti-EPF antibodies. Mouse anti-EPF antiserum titers were evaluated by an indirect enzyme-linked immunosorbent assay (ELISA), and the titers were 6.4 × 103 . Serum samples were taken from 21 Yorkshire × Landrace crossbred sows (12 pregnant and 9 non-pregnant). The presence of EPF in these serum samples was detected by a blocking ELISA using the antigen-antibody (Ag-Abs) reaction between IG20-ovalbumin and mouse anti-EPF antiserum for very early pregnancy diagnosis, blank was used as negative controls. The optical density (OD) values were measured at 450 nm, and the OD ratios of negative control/serum sample (N/S) >2.1 were considered positive, and N/S <2.1 negative. When the test serum samples were in 1/4 dilutions with PBS, twelve samples from pregnant swine were positive, nine non-pregnant serum samples were negative. Very early pregnancy can be determined by using the mouse anti-EPF antiserum blocking ELISA in swine.